Andrographolide suppresses chondrosarcoma cell migration and invasion by inhibiting the PI3K/Akt/mTOR signaling pathway and activating autophagy - Wu, Chun-Fei; Ouyang, Li-xin; Zhang, Wan-hao; Yang, Shuo; Zhong, Xian-Xing; Lin, Yong; Fan, Shuai; Li, Peng; Liang, Zu-Jian (Frontiers in Oncology, 2025)
ObjectiveChondrosarcoma, a malignant bone tumor, exhibits a high incidence rate. This study employed network pharmacology and cell-based experiments to explore the molecular mechanisms by which andrographolide (Andro) suppressed the migration and invasion of chondrosarcoma cells.MethodsAndro’s target genes were identified through integration of data from SuperPred, SEA, STITCH, Pharmmapper, HERB, HIT-2, and Swiss Target Prediction databases, and subsequently cross-referenced with chondrosarcoma-related genes. A protein–protein interaction (PPI) network was constructed using the STRING platform, followed by GO functional annotation and KEGG pathway enrichment analyses of potential targets with R software. Molecular docking assessed the binding affinities between Andro and key targets. Based on network pharmacology data, in vitro experiments validated Andro’s impact on the migration and invasion of chondrosarcoma cells and investigated its underlying mechanisms.ResultsA total of 167 potential targets for Andro were identified. The PPI network highlighted PI3K, Akt, and mTOR as core targets. KEGG pathway analysis revealed that Andro’s inhibitory effects on cell migration and invasion were linked to the PI3K/Akt, HIF-1, and T-cell receptor signaling pathways. Molecular docking confirmed that the binding energies for the Andro-PI3K, Andro-Akt, and Andro-mTOR complexes were<–5 kcal/mol. Wound healing and transwell assays demonstrated that Andro (5 and 20 μM) treatment significantly reduced the wound healing rate and impaired the migratory and invasive abilities of chondrosarcoma cells after 24 hours (p<0.05) compared to controls. Western blotting (WB) analysis showed that Andro (5, 20, and 50 μM) notably downregulated vimentin and MMP-9 expression while upregulating E-cadherin in chondrosarcoma cells (p<0.05 for all). Furthermore, Andro (5, 20, and 50 μM) decreased the p-mTOR/mTOR, p-PI3K/PI3K, and p-Akt/Akt ratios in SW1353 and Hs 819.T cells. WB results also revealed that Andro (5, 20, and 50 μM) reduced p62 expression, while Beclin-1 expression and the LC3A/B-II/LC3A/B-I ratio increased in SW1353 and Hs 819.T cells. Confocal microscopy demonstrated a significant increase in autophagic flux in Andro-treated SW1353 cells. Andro’s effects were attenuated by autophagy inhibitor chloroquine, indicating its pharmacological action via autophagy inhibition in chondrosarcoma cells.ConclusionTherefore, Andro could reduce the migration and invasion of chondrosarcoma cells by modulating the PI3K/Akt/mTOR signaling pathway, alleviating autophagy inhibition, and subsequently promoting autophagic activity.